2012
DOI: 10.2174/157340212803530420
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signals Elicited by GPCR Agonists in Hypertension, Cardiovascular Remodeling: Are MMPs and ADAMs Elusive Therapeutic Targets?

Abstract: Hypertension, the condition characterized by sustained elevated blood pressure, affects over 25% of adults in developed countries and is accompanied by pathological cardiac remodeling (i.e., hypertrophy and fibrosis), thus being a major risk factor for cardiac failure. Life style, the environment, genetic factors, diabetes or obesity can all promote development and progression of hypertension associated cardiovascular disease in part because these conditions induce an excess production of pro-hypertensive, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 213 publications
(273 reference statements)
0
7
0
Order By: Relevance
“…GPCR signals can be fast (ms to s) and transient, sustained and long-lasting (min to hr), or even constitutive, leading to different regulatory cellular mechanisms for adjusting physiological events such as synaptic plasticity [38] or activation of different protein kinases [39]. Changes in the temporal-and spatial-dependent regulation of these signals in particular involving G q -coupled signals can cause different diseases such as inflammatory [40] and cardiovascular [41] disease or addiction, dyskinesia, and obesity [42,43]. Thus, hOpn4L and mOpn4L now offer the opportunity to transiently or sustainably activate GPCR pathways to understand and control different temporally shaped G protein signals in health and disease.…”
Section: Resultsmentioning
confidence: 99%
“…GPCR signals can be fast (ms to s) and transient, sustained and long-lasting (min to hr), or even constitutive, leading to different regulatory cellular mechanisms for adjusting physiological events such as synaptic plasticity [38] or activation of different protein kinases [39]. Changes in the temporal-and spatial-dependent regulation of these signals in particular involving G q -coupled signals can cause different diseases such as inflammatory [40] and cardiovascular [41] disease or addiction, dyskinesia, and obesity [42,43]. Thus, hOpn4L and mOpn4L now offer the opportunity to transiently or sustainably activate GPCR pathways to understand and control different temporally shaped G protein signals in health and disease.…”
Section: Resultsmentioning
confidence: 99%
“…Running Title: MMP-2/HMGCR cardioprotective pathway Xiang Wang (1,5) , Evan Berry (1,5) , Samuel Hernandez-Anzaldo (1,5) , Zamaneh Kassiri (2,3,4,5) and Carlos Fernandez-Patron (1,3,4,5) Xiang Wang, Evan Berry, and Samuel Hernandez-Anzaldo contributed equally.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, GPR62 is a protein‐encoding gene in humans, and GPR62 is related to pathways of the family of G protein–coupled receptors (GPCRs). Numerous research studies have identified associations between GPCRs and hypertensive disorders (Brinks & Eckhart, ; Harris, Cohn, Pesant, & Eckhart, ; Rockman, Koch, & Lefkowitz, ; X. Wang, Bosonea, Odenbach, & Fernandez‐Patron, ), with abnormal GPCR function leading to increased blood pressure (Yang, Villar, Armando, Jose, & Zeng, ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous research studies have identified associations between GPCRs and hypertensive disorders (Brinks & Eckhart, 2010;Harris, Cohn, Pesant, & Eckhart, 2008;Rockman, Koch, & Lefkowitz, 2002;X. Wang, Bosonea, Odenbach, & Fernandez-Patron, 2012), with abnormal GPCR function leading to increased blood pressure (Yang, Villar, Armando, Jose, & Zeng, 2016).…”
Section: Application To Gaw19 Datamentioning
confidence: 99%